Carbapenems as Antidotes for the Management of Acute Valproic Acid Poisoning - Nataša Perković Vukčević; Vesna Mijatović Jovin; Gordana Vuković Ercegović; Marko Antunović; Igor Kelečević; Dejan Živanović; Slavica Vučinić (MDPI AG, 2024)
Introduction: Valproic acid (VPA) is a broad-spectrum drug primarily used in the treatment of epilepsy and bipolar disorder. It is not an uncommon occurrence for VPA to cause intoxication. The established treatment of VPA poisoning includes supportive care, multiple doses of activated charcoal, levocarnitine and hemodialysis/hemoperfusion. There is a clinically significant interaction between carbapenem antibiotics and VPA. By affecting enterohepatic recirculation, carbapenems can increase the overall VPA clearance from the blood of intoxicated patients. It is suggested that carbapenems could successfully be used as antidotes in the treatment of acute VPA poisonings. The aim: To evaluate the effectiveness of carbapenems in the treatment of patients acutely poisoned by VPA. Patients and methods: This retrospective study included patients acutely poisoned by VPA and treated with carbapenems at the Department of Clinical Toxicology at the Military Medicinal Academy in Serbia for a two-year period. Results: After the admission, blood concentrations of VPA kept increasing, reaching their peak at 114-724 mg/L, while the mental state of the patients continued to decline, prompting a decision to introduce carbapenems. After the introduction of carbapenems, the concentrations of the drug dropped by 46-93.59% (average 72%) followed by rapid recovery of consciousness. Ten out of eleven patients had positive outcomes, while one patient died. The most commonly observed complication in our group of patients was bronchopneumonia. Conclusions: The application of carbapenems for the management of acute VPA poisoning might be a useful and effective treatment option.